From molecular genetics to genomics : the mapping cultures of twentieth-century genetics - Gaudillière, Jean-Paul, 1957-; Rheinberger, Hans-Jörg (Routledge, 2004)
With the rise of genomics, the life sciences have entered a new era. This book provides a comprehensive history of molecular genetics and genomics.- Resumé vydavatel
"Second volume of a collection of papers resulting from a conference that was held at the Max Planck Institute for the History of Science in Berlin in March 2001"--Introduction.
Companion vol. to: Classical genetic research and its legacy.
Keywords: molekulární genetika -- dějiny -- 20. století; genomika -- dějiny -- 20. století; molecular genetics -- history -- 20th century; genomics -- history -- 20th century; elektronické knihy; sborníky konferencí; electronic books; proceedings of conferences